Jacob Fellman – the botanising priest - Väre, Henry (Memoranda Societatis pro Fauna et Flora Fennica, 2012)
Amateur botanist Jacob Fellman (1793–1875), priest of northernmost Finland at Utsjoki in 1820– 1831, was the first Finn to study the flora of northernmost East Fennoscandia. He did several long expeditions to Lapponia inarensis (Finland), to East Finnmark (Norway) and to the western Kola Peninsula region (Northwest Russia). His main publications include lists of the species of those areas, as well as their localities and frequencies (J. Fellman 1831, 1835). His memoirs (J. Fellman 1906a) also contain a great deal of plant information. Fellman was also interested in economic plants and phenological observations. During his years at Utsjoki, Jacob Fellman was one of the few botanists to live permanently in northernmost Europe. He became well known early on, maintaining contact with several European botanists and exchanging plants with them. His work, known as ”Herbarium Fellman”, has until now remained uneaxamined. It includes a number of specimens collected by European botanists, comprising altogether 1385 specimens collected mostly in Finland, Germany, Hungary, Norway, Russia and Sweden. Only about 70 specimens collected by Fellman have been placed before in the collections of the Botanical Museum at the University of Helsinki. As a result of the Great Fire of Turku in 1827, in which most of the botanical collection burned. ”Herbarium Fellman” contains important historic specimens of that era. From 1832, Fellman served as a vicar in Lappajärvi, Central Finland. During this second career of his life, his collecting activity nearly ceased. ”Herbarium Fellman” is now incorporated into the main collections at H. All specimens are databased.